Decreation and the ethical bind : Simone Weil and the claim of the other - Cha, Yoon Sook (Fordham University Press, 2017)
In Simone Weil's philosophical and literary work, obligation emerges at the conjuncture of competing claims: the other's self-affirmation and one's own dislocation; what one has and what one has to give; a demand that asks for too much and the extraordinary demand implied by asking nothing. The other's claims upon the self--which induce unfinished obligation, unmet sleep, hunger--drive the tensions that sustain the scene of ethical relationality at the heart of this book.Decreation and the Ethical Bind is a study in decreative ethics in which self-dispossession conditions responsiveness to a demand to preserve the other from harm. In examining themes of obligation, vulnerability, and the force of weak speech that run from Levinas to Butler, the book situates Weil within a continental tradition of literary theory in which writing and speech articulate ethical appeal and the vexations of response. It elaborates a form of ethics that is not grounded in subjective agency and narrative coherence but one that is inscribed at the site of the self's depersonalization.